INTRODUCTION OF ALTERNATIVE (RENEWABLE) ENERGY IN UKRAINE AS A STRATEGIC RESPONSE TO ECONOMIC CHALLENGES IN A SPECIAL PERIOD - Fedir Shulzhenko; Volodymyr Iemelianov; Bohdan Chyzh (Baltic Journal of Economic Studies)
Purpose of the article. This research article highlights the key areas of green energy implementation in Ukraine as a strategic response to current military and economic challenges. The main focus is on the analysis of the potential of renewable energy sources and their impact on energy security and sustainable development of the country. Object of the article. The article examines the processes of integration of renewable energy into the national energy system. The subject of the analysis is the introduction of "green" energy as a basis for ensuring Ukraine's energy independence. Methodology. The research methods include a systematic approach to analysing the potential of renewable energy sources, comparative legal analysis to assess regulatory initiatives, and modelling the economic impact of renewable energy integration. An important role is also played by statistical analysis and forecasting methods, which allow to assess future developments in the energy sector. Practical implications. Strengthening national security by reducing dependence on imported energy resources and increasing the share of renewable energy in the country's energy balance. Value / Originality. The study contributes to the understanding of the importance of green energy as a strategic response to the challenges of a special period. The paper offers specific recommendations on policies and mechanisms for implementing effective renewable energy solutions. Results. It is determined that the introduction of green energy should include strategic planning and the use of innovative technologies for efficient resource management. Significant investments are required from the state budget of Ukraine, local budgets and the private sector. At the same time, strategic resource management should take into account the interests of all parties, ensuring the stability and reliability of critical infrastructure.